2003
DOI: 10.1592/phco.23.5.643.32199
|View full text |Cite
|
Sign up to set email alerts
|

Mississippi Mud No More: Cost‐Effectiveness of Pharmacokinetic Dosage Adjustment of Vancomycin to Prevent Nephrotoxicity

Abstract: Although pharmacokinetic monitoring and dosage adjustment are effective methods for reducing the toxicity of many drugs, controversy exists regarding the necessity of such monitoring with vancomycin. Evaluation by decision analysis over a range of assumptions, varying probabilities, and costs reveals that pharmacokinetic monitoring and vancomycin dosage adjustment to prevent nephrotoxicity are not cost-effective for all patients. However, such dosage adjustment demonstrates cost-effectiveness for patients rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 21 publications
3
38
0
1
Order By: Relevance
“…The previous similar studies results were associated with shorter courses of therapy, less total doses of vancomicin and hospital stay [6,19,21]. In our work, there was a significant improvement in response achievement (p=0.015) in monitored group compared to non-monitored group.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The previous similar studies results were associated with shorter courses of therapy, less total doses of vancomicin and hospital stay [6,19,21]. In our work, there was a significant improvement in response achievement (p=0.015) in monitored group compared to non-monitored group.…”
Section: Discussionsupporting
confidence: 79%
“…On the other hand, vancomycin monitoring decreased the nephrotoxicity in VWM group compared to VWOM group (p=0.016) and reached a similar result of VF group [6,19,21]. This findings support the idea of monitoring vancomycin when added to the treatment of pediatric cancer patients.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…1,2 Increasing evidence suggests that the current use of TDM is suboptimal, with up to 70% to 80% of drug quantifications in hospitalized patients being inappropriately performed, primarily because of routine daily monitoring without pharmacological justification. 3,4 Routine vancomycin TDM has been intensely debated, [5][6][7][8][9] and scrutiny has resulted in the publication of consensus guidelines in January 2009 by the American Society of Health-System Pharmacists, the Infectious Disease Society of America, and the Society of Infectious Disease Pharmacists. 1 These guidelines focused specifically on vancomycin TDM in adult patients.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] It was reported that the adverse drug reactions of norvancomycin are similar to vancomycin, such as nephrotoxicity, ototoxicity, rash and itching. [4][5][6][7][8][9][10] Nephrotoxicity will result in serious consequences, especially in the patients who are aged, have kidney diseases or receive concomitant medication excreted from kidney such as aminoglycosides. 8,[11][12][13][14] So, norvancomycin treatment should be supported by TDM and individualized dosing regimen to decrease the occurrence of adverse reactions and improve efficacy.…”
Section: Introductionmentioning
confidence: 99%